Effect of Reward System on Male Participation in Surgical Contraceptive Method - Suwarsi Suwarsi; Casnuri Casnuri; Fika Lilik Indrawati; Merita Eka Rahmuniyati (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2018)
Introduction: The participation of men in the surgical contraceptive method (MOP) has not increased even though in some regencies or cities in Indonesia. There has been a reward program for men who want to join the MOP. This study was to determine the relationship of interest with the reward system for prospective MOP acceptors. Methods: Quantitative study with observational analytic approach, cross-sectional time design with two groups. The total sample of 60 men was taken by purposive sampling according to the inclusion criteria. Data is taken through a measuring instrument in the form of a questionnaire.  Bivariate analysis with chi-square test. Results: Respondents 'interest in family planning MOP in no system reward was mostly low at 21 people (70%), while the respondents' interest in family planning MOP in system reward was mostly good at 18 people (60%). There is no difference in interest in prospective MOP family planning acceptors between Districts with reward system and without reward system. There is a correlation between interest and reward (p = 0.007) in the Regency with reward and without reward system. Conclusions: There is no difference in interest between candidates for Family Planning MOP acceptors between reward and without reward system.